A study on extruded filament bonding in fused filament fabrication. Issue 3 (27th November 2018) - Costa, Ana Elisa; Ferreira da Silva, Alexandre; Sousa Carneiro, Olga
Abstract : Purpose: The performance of parts produced by fused filament fabrication is directly related to the printing conditions and to the rheological phenomena inherent to the process, specifically the bonding between adjacent extruded paths/raster. This paper aims to study the influence of a set of printing conditions and parameters, namely, envelope temperature, extrusion temperature, forced cooling and extrusion rate, on the parts performance. Design/methodology/approach: The influence of these parameters is evaluated by printing a set of test specimens that are morphologically characterized and mechanically tested. At the morphological level, the external dimensions and the voids content of the printed specimens are evaluated. The bonding quality between adjacent extruded paths is assessed through the mechanical performance of test specimens, subjected to tensile loads. These specimens are printed with all raster oriented at 90º relative to the tensile axis. Findings: The best performance, resulting from a compromise between surface quality, dimensional accuracy and mechanical performance, is achieved with a heated printing environment and with no use of forced cooling. In addition, for all the conditions tested, the highest dimensional accuracy is achieved in dimensions defined in the printing plane. Originality/value: This work provides a relevant result as the majority of the current printers comes without enclosure or misses the heating and envelope temperature control systems, which proved to be one of the most influential process parameter.